2012
DOI: 10.21608/jpp.2012.84057
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Elite Aromatic Rice Varieties Under Different Sowing Dates Under Egyptian Condition

Abstract: The obtained results showed that rice plants sown on the second date (May 10 th) surpassed those which sown on the late date of sowing (June 10 th) in plant height, leaf area index, dry matter accumulation (g m-2), tillers number m-2 , panicle number m-2 , number of filled grains panicle-1 , 1000-grain weight, straw yield and grain yield as well as aromatic level in both seasons. There was no significant difference between rice sown on the April 24 th or May 10 th in the most studied traits. Delay in sowing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…LU Chuan-gen et al (2007) indicated that among the climatic factors which affected rice spikelet fertility as well as grain yield, the key factor is air temperature. Similar results were also reported by Metwally et al (2012), Rajesh Khavse et al (2015 and Metwally et al (2016). Table 15 presents number of days to heading of the studied rice genotypes under different sowing dates.…”
Section: Resultssupporting
confidence: 85%
“…LU Chuan-gen et al (2007) indicated that among the climatic factors which affected rice spikelet fertility as well as grain yield, the key factor is air temperature. Similar results were also reported by Metwally et al (2012), Rajesh Khavse et al (2015 and Metwally et al (2016). Table 15 presents number of days to heading of the studied rice genotypes under different sowing dates.…”
Section: Resultssupporting
confidence: 85%
“…The height of plant shows no statistical significant differences among sowing dates other than 29 July. The height of variety shows decreasing trend with further delayed sowing (14 July and 29 July) in agreement with (Metwally et al, 2012) who reported decreased plant height due to delayed sowing in two rice growing seasons under Egyptian condition. The similar findings were also reported by (Safdar et al, 2013), (Begum et al, 2018), (Walia et al, 2014) and (Ferrari et al, 2018).…”
Section: Plant Heightsupporting
confidence: 89%
“…Tashiro et al (1999) reported a good seedling establishment when planting rice at early sowing date, to ensure an appropriate temperature during seed germination at seedling emergence. Metwally et al (2012) found that rice plants sown on May 1 st surpassed those grown on June 1 st in most of rice plant characters considered in our investigation. Osman (2019) obtained results in the same line, when 14 rice genotypes were evaluated at the experimental farm of Rice Research and Training Center, Sakha, Egypt.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, grain filling coincides milder temperatures consequently, good grain quality (Farrell et al, 2003 andPatel et al, 2019). Metwally et al, (2012) and Osman (2019) reported that early rice sowing, early May enhances plant height, number of panicles/hill, number of filled grains/ panicle and rice grain yield.…”
Section: Introductionmentioning
confidence: 99%